Feasibility study of advanced focused cardiac measurements within the emergency department - Betcher, Joe (Crit Ultrasound J, 2018)
BACKGROUND: This study aims to compare the increased time needed to perform advanced focused cardiac measurements in the emergency department, including diastolic heart failure evaluation via E/E′, and cardiac output with LVOT/VTI. Patients with pertinent cardiopulmonary symptoms in the emergency department had a focused cardiac ultrasound performed by the emergency department ultrasound team. The ability to obtain basic cardiac windows, evaluate for effusion, systolic ejection fraction, and right-sided heart pressures were recorded. Advanced measurements, along with time to obtain all images and the training level of the provider, were recorded. RESULTS: Fifty-three patients were enrolled. Basic focused cardiac windows were able to be obtained in 80% of patients. The average 4-window focused cardiac ultrasound took 4 min and 49 s to perform. Diastolic measurements were able to be obtained in 51% of patients, taking an average of 3 min and 17 s. Cardiac output measurements were able to be obtained in 53% of patients, taking an average of 3 min and 8 s. CONCLUSION: The ability to obtain these images improved with increasing level of training. Performing both cardiac output and diastolic measurements increased the time with bedside ultrasound by 6 min and 25 s, and were able to be obtained in slightly over half of all ED patients.